Analisis Pengaruh Pertumbuhan Ekonomi terhadap Kesejahteraan Masyarakat di Kota Bandar Lampung Periode 2013-2023 - Luluk Sulastri; Putri Handayani; Syariful Alawiyah; M. Yusuf Bahtiar (Indo Publishing, 2026)
This study analyzes the effect of economic growth on community welfare in Bandar Lampung City for the period 2013–2023. Using a quantitative approach with secondary data from BPS (Statistics Indonesia) Bandar Lampung and the Regional Development Planning Agency (Bappeda), this research employs simple linear regression analysis and the Human Development Index (HDI) as the primary welfare indicator. The results show that economic growth has a significant and positive effect on community welfare in Bandar Lampung City. A 1% increase in economic growth leads to an increase in the HDI by 0.42 points. The average HDI of Bandar Lampung reached 75.23 during the study period, placing it in the high human development category. However, the pace of HDI improvement does not always align proportionally with economic growth rates, indicating that growth inclusivity and equitable distribution remain key policy challenges. The findings suggest that policymakers should prioritize pro-poor growth strategies and strengthen social protection programs to ensure that economic growth effectively translates into improved community welfare.